Anemia in patients with coinherited thalassemia and glucose-6-phosphate dehydrogenase deficiency - Sakorn Pornprasert (2018)
Thalassemia and glucose-6-phosphate dehydrogenase (G-6-PD) deficiency are genetic disorders that cause hemolytic anemia. In areas with high frequencies of both hematological disorders, coinheritance of G-6-PD deficiency with thalassemia can be found. Whether G-6-PD deficiency, coinherited with thalassemia, enhances severe anemia is still unclear. Hematological parameters between thalassemia carriers with G-6-PD deficiency and those without G-6-PD deficiency were compared. The G-6-PD deficiency was diagnosed in 410 blood samples from thalassemia patients using a fluorescent spot test. The levels of hemoglobin (Hb), packed cell volume (PCV), mean corpuscular volume (MCV) and Hb A2/Hb E [β26(B8)Glu→Lys; HBB: c.79G > A] were measured using an automated blood counter and high performance liquid chromatography (HPLC), respectively. The G-6-PD deficiency was found in 37 samples (9.02%). Mean levels of Hb, PCV, MCV and Hb A2/E were similar between the two groups. Thus, G-6-PD deficiency did not enhance red blood cell pathology or induce more anemic severity in thalassemia patients. © Informa Healthcare USA, Inc.